The construction process of the painting class as a process of creation and research in visual arts (Revista Apotheke, 2023)
The present essay consists of a visual report of the oriented teaching of the Master in the Post-Graduation Program in Visual Arts of the State University of Santa Catarina - UDESC, in the discipline of Pictorial Processes in the Graduation in Visual Arts in the classes of licenciatura and baccalaureate, taught by Prof. Dr. Jociele Lampert in the second half of 2022 at the same educational institution. Taking Pablo Picasso as a reference artist for the creation of a proposal/challenge for undergraduate classes and the idea of the studio as a living space. The studio space, as a place of articulation and relations between teaching and learning in Visual Arts. Doing and practice as a generating element of knowledge production in Art. For, from the understanding of the author Dewey (2010) about aesthetic experience, theory and practice are not separate elements, but generators of knowledge, learning through doing.
Keywords: Visual reporting; Experience; Pablo Picasso; Collage